Effect of Seed Bulb Cutting Size and Planting Media Volume on the Growth and Yield of Shallot (Allium ascalonicum L.) under a Hydroponic Wick System - Muhammad Fahri Rizaldi; Ramdan Hidayat; Hadi Suhardjono (The University of Lampung, 2025)
Shallots (Allium ascalonicum L.) are cultivated as a high economic value agricultural business. Cutting the tip of the seed bulb can stimulate, accelerate and synchronize plant growth. In hydroponic cultivation, the volume of planting media is an important component that needs to be considered. This research was conducted at the Greenhouse Hydroponic Farm Lamongan, Lamongan District, Lamongan Regency, East Java. Split plot design (RPT) or split plot design in a Completely Randomized Design (CRD) with the main plot (main plot) the volume of planting media (U) with 3 levels: 10cm (U1), 15cm (U2), 20cm (U3) and sub plots (sub plots) are the size of the cutting of the seed bulbs (P) with 4 levels: not cut (P0), cut 1/4 (P1), cut 1/3 (P2), cut 1/2 (P3). It was found that the treatment of the size of the cutting of the seed bulbs affected the vegetative and generative variables. Meanwhile, the treatment of planting media volume affects generative variables, especially on the number of harvested bulbs per box and the weight of harvested bulbs per box. The most optimal interaction between the combination of the size of cutting seed bulbs and the volume of planting media occurs at the size of cutting seed bulbs of 1/4 part and the volume of planting media of 10 cm, which is able to increase the weight of harvested bulbs per clump.